Knowledge and practices regarding the use of medicinal plants during pregnancy in Costa Rica - Sandra Henández-Salón; Denyer Sánchez-Pérez; Javier Alonso León-Chavarría; Nicol García-Carvajal (Maskana)
This study aims to identify the knowledge and practices regarding the use of medicinal plants and analyze how gender and educational level influence such knowledge and practices during pregnancy in Costa Rica, addressing research gaps. A total of 144 individuals aged 20 to 49 were surveyed. 59% of respondents were aware of the risks associated with the use of medicinal plants during pregnancy, with women showing greater knowledge than men. A higher educational level was associated with greater concern about risks such as abortion and fetal malformations. The most commonly used plants were Matricaria chamomilla, Ruta graveolens, Satureja viminea, and Zingiber officinale, with leaves being the most frequently used part and infusions the most common preparation method. These plants were primarily used to treat nausea and gastrointestinal issues. The study concluded that further research is needed to guide healthcare professionals and the public on the safe use of medicinal plants during pregnancy in Costa Rica.